Vadybinės kompetencijos žinių visuomenės iššūkių kontekste - Diskienė, Danuta; Marčinskas, Albinas; Stankevičienė, Asta (Information & Media, 2010)
Perėjimo į informacijos amžių sąlygomis intelektiniai ištekliai tampa gerokai reikšmingesni nei fiziniai. Vadovai turi ne tik mokėti ugdyti žinias, auginti jas kaip kadaise kapitalą, bet ir mokėti vadovauti turintiems tas žinias darbuotojams. Todėl besivystančios žinių visuomenės sąlygomis vadybiniam darbui keliami nauji iššūkiai, o žinios tampa esminiu organizacijos ištekliumi. Straipsnyje pabrėžiamas žinių visuomenės koncepcijos aktualumas, jos plėtros sąsaja su kompetencija kaip esmine žmogiškojo kapitalo dedamąja. Remiantis Lietuvos verslo sektoriaus vadovų vadybinės kompetencijos tyrimo rezultatais, analizuojamos vadovų kompetencijos žinių visuomenės kontekste. Managerial Competences in the Context of Knowledge Society Challenges Danuta Diskienė, Albinas Marčinskas, Asta Stankevičienė Summary The transformation to the information century implies the importance of escalating intellectual rather than physical recourses. Leaders ought to expand knowledge, raise it as capital, and have an ability to manage employees with such knowledge. Therefore, the conditions of developing knowledge society raise new challenges for management, and knowledge becomes an essential recourse of an organization. This article seeks to evaluate the managerial competences of leaders in the context of developing knowledge society. To this end, the article discusses various interpretations of the concept of knowledge society and the problems of managerial competence. This article invokes research results of leaders’ managerial competence study in Lithuania’s business sector. These results show that leaders do not posses adequate competence in all fields and are prepared only partially for the challenges of knowledge society. Therefore, formation of the national leaders’ competence development programme oriented towards the topicality of knowledge society development is expedient. /span>